PERLINDUNGAN HUKUM TERHADAP KONSUMEN JUAL BELI MOBIL BEKAS DIKECAMATAN PONTIANAK UTARA - NIM. A1012201097, CRISTIN ANDREA (Fakultas Hukum Universitas Tanjungpura, 2025)
ABSTRACT Consumer protection is an inseparable part of healthy business activities. The absence of balanced protection causes consumers to be in a weak position. The losses experienced by consumers can arise as a result of the legal relationship between the producer and the consumer, or as a result of unlawful acts committed by the producer. The study on